Composite electrode having a hydrogel-containing membrane and method for producing the composite electrode

By using hydrogel to form a non-porous separator in the composite electrode, the problems of short available life and measurement error of the composite electrode are solved, achieving longer service life and higher measurement accuracy.

JP7650799B2Active Publication Date: 2025-03-25HAMILTON BONADUZ AG
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021533420
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-13
Filing Date
2019-12-10
Publication Date
2025-03-25
Estimated Expiration
2039-12-10

AI Technical Summary

Technical Problem

The available lifespan of existing composite electrodes is short, prone to measurement errors due to KCl efflux and contamination, and needs to be stored in a wet environment to reduce KCl efflux.

Method used

Using a composite electrode design with hydrogel, by introducing dry hydrogel into the electrode opening and contacting the first conductive fluid, it is expanded to close the opening, forming a non-porous separator, reducing KCl outflow and improving anti-pollution ability.

Benefits of technology

The service life of the composite electrode is extended, measurement errors are reduced, the need to be stored in a wet environment, and good performance can be maintained under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007650799000023
    Figure 0007650799000023
  • Figure 0007650799000024
    Figure 0007650799000024
  • Figure 0007650799000025
    Figure 0007650799000025
Patent Text Reader

Abstract

The present invention relates to a composite electrode (1), preferably a pH glass electrode, for measuring a fluid to be measured, comprising a working electrode (2), a reference electrode (3), a diaphragm (10) preferably comprising a thermoplastic polyurethane block copolymer, and a first conductive fluid (6) in contact with the reference electrode (3) and the diaphragm (10) such that the diaphragm (10) is electrically connected to the reference electrode (2) via the first conductive fluid (6), the diaphragm comprising a hydrogel. The present invention also relates to a method for producing the composite electrode (1).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite electrode and a method for producing the same. [Background technology]

[0002] A combination electrode is a working electrode and a reference electrode housed in one rod. The term measuring electrode is used synonymously with working electrode. A combination electrode can be, for example, a redox sensor or a pH combination electrode, which can be used to determine the pH value. A pH combination electrode can be, for example, a pH glass electrode.

[0003] The reference electrode is often a metal wire immersed in saline. The reference electrode is often a silver-silver chloride electrode with a silver wire coated with an AgCl layer, which is immersed in a KCl solution. The KCl solution is separated by a diaphragm. When the combined electrode is in operation, the diaphragm is in contact with the measured fluid. The diaphragm is characterized by preventing mixing of the KCl solution and the measured fluid and allowing charge transport between the KCl solution and the measured fluid. To allow charge transport, the diaphragm has traditionally been made porous. However, the porous structure of the diaphragm has the disadvantage that the surface area of ​​the diaphragm is large and prone to contamination over time. Contamination makes it difficult for charges to move, which can lead to errors in measurements using the combined electrode.

[0004] In addition, there is a problem of KCl escaping from the composite electrode through the diaphragm, which is manifested by the formation of efflorescence of KCl on the outside of the diaphragm. This changes the KCl concentration of the KCl solution, which in turn changes the electrochemical potential of the reference electrode. The change in potential introduces further errors into the measurement. Even if the mass of KCl escaping from the composite electrode is small, it takes a correspondingly long time to produce an erroneous measurement. To reduce the mass flow rate of KCl escaping from the composite electrode, it was previously necessary to store the composite electrode in a liquid that wets the diaphragm from the outside of the composite electrode. Due to the increasing contamination and the escaping of KCl, the composite electrode has a limited service life within which it can perform error-free measurements. The prior art documents relevant to the invention of this application are as follows (including documents cited during the international phase after the international filing date and documents cited when the application entered the national phase in other countries). (Prior art document) (Patent Documents) (Patent Document 1) German Patent Application Publication No. 102009055092 (Patent Document 2) U.S. Patent Application Publication No. 2005 / 133369 (Patent Document 3) European Patent Application Publication No. 1172648 (Patent Document 4) German Patent Application Publication No. 69526366 (Patent Document 5) International Publication No. 2006 / 018425 (Non-Patent Literature) (Non-patent document 1) FERREIRA NN ET AL:"Recent advances in smart hydrogels for biomedical applications: From self-assembly to functional approaches",EUROPEAN POLYMER JOURNAL,PERGAMON PRESS LTD.OXFORD,GB,Vol.99,6 December 2017 (2017-12-06),pages 117-133 Summary of the Invention

[0005] The problem to be solved by the present invention is therefore to create a composite electrode and a method for manufacturing the same, which can extend the service life of the composite electrode and allow error-free measurements to be performed within that service life.

[0006] A composite electrode according to the present invention for measuring a fluid to be measured comprises a working electrode, a reference electrode, a diaphragm, and a first conductive fluid in contact with the reference electrode and the diaphragm such that the diaphragm is electrically connected to the reference electrode via the first conductive fluid, the diaphragm comprising a hydrogel.

[0007] Surprisingly, it was found that the composite electrode according to the invention has a much lower outflow of the first conductive fluid through the diaphragm than a conventional composite electrode with a porous diaphragm. However, at the same time, charge transport between the first conductive fluid and the fluid to be measured is possible. Due to the absence of pores, the hydrogel is less susceptible to contamination that makes charge transport more difficult. The low outflow of the first conductive fluid and the low contamination of the hydrogel result in a long service life of the composite electrode, during which the composite electrode can perform error-free measurements. Furthermore, due to the low mass flow rate of the first conductive fluid leaving the composite electrode through the diaphragm, the composite electrode does not need to be stored in liquid. Furthermore, since the hydrogel is elastic, it is possible to compensate for temperature fluctuations, so that the composite electrode remains sealed. Furthermore, this composite electrode is easy to manufacture in that the hydrogel is introduced in a dry state into the opening of the composite electrode, and then the hydrogel is brought into contact with the first conductive fluid, whereby the hydrogel swells and seals the opening. The contacting of the first conductive fluid with the hydrogel can be performed at the same time as filling the composite electrode with the first conductive hydrogel.

[0008] Due to the low outflow of KCl, no crystals form on the diaphragm. This is a prerequisite for the composite electrode to comply with GMP (Good Manufacturing Practice) guidelines. It was also possible to show that the composite electrode can be sterilized by gamma radiation without impairing the functionality of the composite electrode, especially the diaphragm. This composite electrode is therefore suitable for use in fermenters, especially disposable fermenters. The problem with conventional porous diaphragms is that if the measured fluid contains sulfides, silver sulfide precipitates and blocks the pores of the diaphragm, making the charge transport between the first conductive fluid and the measured fluid difficult and resulting in an erroneous measurement. However, in the case of a diaphragm with a hydrogel, silver sulfide still precipitates in the diaphragm, but as a result, further conductive fluids, especially water, will diffuse into the diaphragm. As a result, the diaphragm continues to swell, facilitating the charge transport between the first conductive fluid and the measured fluid.

[0009] The hydrogel preferably comprises a thermoplastic polyurethane. In particular, the hydrogel essentially consists of a thermoplastic polyurethane. The thermoplastic polyurethane is preferably made of monomer A. [ka] and Monomer B [ka] It is a block copolymer having the following structure:

[0010] The monomers are in each case formed by the region extending from the left bracket to the right bracket. In the block copolymer, the block copolymer can be terminated by attaching an oxygen atom to the left side of monomer A or by attaching a hydroxy group to said left side. The block copolymer can be terminated by attaching a carbon atom to the right side of monomer A or by attaching a hydrogen atom to said right side. The block copolymer can be terminated by attaching an oxygen atom to the left side of monomer B or by attaching a hydroxy group to said left side. The block copolymer can be terminated by attaching a carbon atom to the right side of monomer B or by attaching a hydrogen atom to said right side. The block copolymer can essentially consist of a block of monomer A and a block of monomer B and a terminal group for terminating the block copolymer. The terminal group can be a hydroxy group as described above and / or a hydrogen atom as described above.

[0011] The mass ratio of monomer B to monomer A is preferably in the range of 20-100, particularly 30-90.

[0012] TIFF0007650799000003.tif7167 especially 80*10 3 g / mol~150*10 3 It is preferably in g / mol. TIFF0007650799000004.tif16160 where n is the number of polymer chains in the block copolymer and Mi is the molar mass of polymer chain i.

[0013] This block copolymer is commercially available from Lubrizol under the trade name Tecophilic®. An example may be Tecophilic® TG-500 and / or Tecophilic® TG-2000. The mass ratio of monomer B to monomer A is about 40 for Tecophilic® TG-500 and about 82 for Tecophilic® TG-2000. TIFF0007650799000005.tif5142Tecophilic (registered trademark) TG-500: approx. 1.4*10 5 g / mol, approximately 8*10 for Tecophilic® TG-2000 4 g / mol.

[0014] For example, the hydrogel may have a polymer used in soft contact lenses. Examples include hydroxyethyl methacrylate, methyl methacrylate, vinylpyrrolidone and / or silicone hydrogels. The hydrogel may be a thermoplastic elastomer. The hydrogel may be a smart hydrogel. In particular, the smart hydrogel may be ionic strength responsive and / or thermally responsive. An example of a smart hydrogel that is both ionic strength responsive and thermally responsive is the aforementioned Tecophilic®. Another example of a thermally responsive smart hydrogel is a polymer based on N-isopropylacrylamide copolymer.

[0015] The hydrogel is preferably a thermoplastic elastomer. In contrast to other elastomers, thermoplastic elastomers can be extruded into a film and subsequently the diaphragm can be punched out of the film. In contrast to conventional thermoplastics, thermoplastic elastomers maintain their elastic properties even at room temperature. An example of a thermoplastic elastomer is a block copolymer.

[0016] It is preferable that the hydrogel is a smart hydrogel, i.e., a hydrogel that responds to stimuli. A smart hydrogel is characterized by undergoing a significant volume change in response to a specific environmental condition. It is particularly preferable that the smart hydrogel is ionic strength responsive and / or thermally responsive. When the smart hydrogel is ionic strength responsive, the smart hydrogel swells further, and the salt concentration or conductivity of the measured fluid decreases. An example of such an ionic strength responsive smart hydrogel is the above-mentioned block copolymer. When the salt concentration of the measured fluid is low, the ions of the first conductive fluid diffuse more into the measured fluid through the swelled diaphragm, so that the diffusion potential between the first conductive fluid and the measured fluid decreases, and the measurement accuracy improves. In this way, a composite electrode having a smart hydrogel that is ionic strength responsive is suitable for measuring ultrapure water. In addition, when the smart hydrogel is thermally responsive, it can be designed to shrink as the temperature increases. An example of such a thermally responsive smart hydrogel is the above-mentioned block copolymer. The contraction of the smart hydrogel makes it less susceptible to contamination and reduces the escape of ions from the first conductive fluid, thereby extending the service life of the composite electrode even at high temperatures.Another example of a thermoresponsive smart hydrogel is a polymer based on N-isopropylacrylamide copolymers.

[0017] The composite electrode preferably has a reference space in which the first conductive fluid is arranged and an opening in which a diaphragm is arranged and sealed by the diaphragm. The opening can be particularly easily and particularly firmly sealed by the diaphragm by first introducing a hydrogel into the opening in a dry state. After contact with the first conductive fluid, the hydrogel swells and can thus seal the opening.

[0018] The composite electrode preferably has an outer tube and an inner tube disposed within the outer tube, the reference space being disposed between the outer tube and the inner tube, and the opening being an annular gap between the outer tube and the inner tube. The hydrogel can be easily shaped into an annular shape, for example by cutting and / or punching, so that the annular gap can also be sealed with the hydrogel.

[0019] The composite electrode preferably has a plug that is permeable to the measured fluid and is arranged in the opening to support the diaphragm. To ensure that the plug is permeable to the measured fluid, it can have, for example, a through hole, a groove, a porosity, etc. The plug can be arranged on the side of the diaphragm facing the reference space and / or on the side of the diaphragm facing away from the reference space. The provision of the plug can prevent the diaphragm from slipping out of the opening, in particular when the first conductive fluid is introduced into the reference space. It is also possible to control the outflow of the first conductive fluid using the plug, for example by selecting the diameter and / or number of the through holes, the size of the groove, the porosity of the plug, and / or the dimensions of the plug.

[0020] It is preferred that the inner tube has a first inner tube longitudinal end designed to be closed and a glass membrane, and a second conductive fluid that brings the glass membrane into contact with the working electrode is disposed within the inner tube such that the glass membrane is electrically connected to the working electrode via the second conductive fluid.

[0021] The composite electrode is preferably a pH composite electrode and / or a redox sensor. The pH composite electrode is particularly preferably a pH glass electrode.

[0022] The first conductive fluid may be an aqueous KCl solution, for example a 3M KCl solution. Alternatively, the first conductive fluid may be a highly viscous liquid. For example, the aqueous KCl solution, in particular a 3M KCl solution, may in this case be thickened with a thickener, in particular hydroxyethyl cellulose. Hydroxyethyl cellulose is, for example, commercially available under the trade name Natrosol. Alternatively, the first conductive fluid may be strongly solidified. For this purpose, a monomer mixture is introduced into the composite electrode and polymerized to form a polymer. The polymer may be, for example, a polymer obtained by polymerizing N-acryloylaminoethoxyethanol, or a polymer obtained by copolymerizing N-acryloylaminoethoxyethanol with hydroxyalkyl methacrylate, as described in WO 2005 / 073704 A1.

[0023] The thickness of the diaphragm is preferably in the range of 0.1 mm to 1.0 mm, particularly 0.35 mm to 0.7 mm. It has been found that with these thicknesses, the outflow of KCl is small, but the charge exchange between the first conductive fluid and the fluid to be measured is very high, making it possible to perform error-free measurements using the composite electrode.

[0024] The method according to the invention for producing a composite electrode comprises the following steps: providing an outer tube and an inner tube arranged in the outer tube, a reference space being arranged between the outer tube and the inner tube, the outer tube and / or the inner tube defining an opening, placing a working electrode in the inner tube and a reference electrode in the outer tube, introducing a hydrogel in a dry state into the opening, the hydrogel defining the reference space, introducing a first conductive fluid into the reference space and bringing the hydrogel into contact with the first conductive fluid, whereby the hydrogel swells to form a diaphragm and seals the opening, and bringing the reference electrode into contact with the first conductive fluid, the diaphragm being electrically connected to the reference electrode via the first conductive fluid. The method according to the invention allows the opening to be sealed easily and particularly robustly. The composite electrode produced by this method has a long service life, during which it is capable of performing error-free measurements. The placement of the working electrode in the inner tube and the reference electrode in the outer tube can be performed both before and after the introduction of the hydrogel.

[0025] The outer tube preferably has a first outer tube longitudinal end in the area where the diaphragm is located and a second outer tube longitudinal end where the first conductive fluid is introduced into the reference space.

[0026] Alternatively, it is preferred that the outer tube has a first outer tube longitudinal end in the area where the diaphragm is located and a second outer tube longitudinal end, and the method comprises the following steps: sealing the second outer tube longitudinal end before introducing the first conductive fluid into the reference space, and immersing the first outer tube longitudinal end in the first conductive fluid to introduce the first conductive fluid into the reference space, introducing the composite electrode together with the first conductive fluid into a vacuum vessel, evacuating and then ventilating the vacuum vessel so that the first conductive fluid enters the reference space through the opening. This is a simple method for filling the reference space. It is also possible to simultaneously immerse multiple composite electrodes in the first conductive fluid and introduce the composite electrodes into the vacuum vessel in order to evacuate and ventilate the vacuum vessel. As a result, the first conductive fluid can be introduced into multiple composite electrodes simultaneously, making the method cost-effective. In particular, it is preferred that the vacuum vessel is evacuated to a pressure of 50 mbar to 100 mbar, in particular 80 mbar.

[0027] It is preferred that the inner tube has a first inner tube longitudinal end designed to be closed and a glass membrane arranged in the region of the first inner tube longitudinal end, and a second conductive fluid that brings the glass membrane into contact with the working electrode is arranged in the inner tube in such a way that the glass membrane is electrically connected to the working electrode via the second conductive fluid. Particularly preferably, the first inner tube longitudinal end is arranged in the region of the first outer tube longitudinal end.

[0028] When introducing the hydrogel in the dry state into the opening, it is preferable to select the hydrogel so that it is smaller than the opening, so that after the first conductive fluid is introduced into the reference space, a compressive stress is applied to the formed diaphragm. As a result, the opening can be sealed particularly tightly. In order to ensure the generation of the compressive stress, a person skilled in the art can carry out preliminary tests using hydrogels of various sizes smaller than the opening in the dry state, which can be brought into contact with the first conductive fluid and swollen. After swelling, the size of the hydrogel in the swollen state is determined, and among the various sizes of hydrogels, only those that are larger than the opening in the swollen state are suitable for the diaphragm. Among the various sizes of hydrogels, it is possible to select those that are 10% to 100% larger than the opening in the swollen state, in particular those that are 30% to 50% larger. The swelling degree Q of the hydrogel can be in the range of 115% to 1000%, in particular 150% to 800%, in particular 180% to 350%. The swelling degree Q can be calculated as Q=(V Q -V T ) / V T is defined as V T is the volume of the hydrogel in the dry state, and V Q is the volume of the hydrogel swollen with the first conductive fluid. [Brief description of the drawings]

[0029] In the following the invention will be explained in more detail with the aid of the attached schematic drawings. [Figure 1] FIG. 1 is a longitudinal sectional view of a composite electrode. [Diagram 2] FIG. 2 shows plots of potassium flux for various composite electrodes. [Diagram 3] Figure 3 shows plots of potassium flux for various composite electrodes and two different temperatures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] The composite electrode 1 can be a pH composite electrode and / or a redox sensor. The pH composite electrode can be a pH glass electrode.

[0031] As can be seen from FIG. 1, the composite electrode 1 includes a working electrode 2, a reference electrode 3, a diaphragm 10, and a first conductive fluid 6 for measuring a fluid to be measured. The first conductive fluid is in contact with the reference electrode 3 and the diaphragm 10 such that the diaphragm 10 is electrically connected to the reference electrode 2 via the first conductive fluid 6. In order to perform a measurement in the operation of the composite electrode 1, it is necessary to contact the surface of the diaphragm 10 facing away from the first conductive fluid 6 with the fluid to be measured. The diaphragm 10 is characterized in that it prevents the first conductive fluid 6 and the fluid to be measured from intermixing with each other, while enabling charge transport between the first conductive fluid 6 and the fluid to be measured. Furthermore, the composite electrode 1 includes a glass membrane 9 and a second conductive fluid 7 that electrically connects the glass membrane 9 and the working electrode 2. The first conductive fluid 6 and the second conductive fluid 7 are electrically insulated from each other. The fluid to be measured is also brought into contact with the surface of glass membrane 9 facing away from second conductive fluid 8, and the electric voltage between working electrode 2 and reference electrode 3 is measured.

[0032] In accordance with the present invention, the diaphragm 10 comprises a hydrogel, or the diaphragm 10 can consist essentially of a hydrogel.

[0033] The hydrogel can comprise a thermoplastic polyurethane. The thermoplastic polyurethane can be a mixture of monomers A, B, C, and D. [ka] and Monomer B [ka] The block copolymer may be a block copolymer having the formula:

[0034] The monomers are in each case formed by the region extending from the left bracket to the right bracket. In the block copolymer, the block copolymer can be terminated by attaching an oxygen atom to the left side of monomer A or by attaching a hydroxy group to said left side. The block copolymer can be terminated by attaching a carbon atom to the right side of monomer A or by attaching a hydrogen atom to said right side. The block copolymer can be terminated by attaching an oxygen atom to the left side of monomer B or by attaching a hydroxy group to said left side. The block copolymer can be terminated by attaching a carbon atom to the right side of monomer B or by attaching a hydrogen atom to said right side. The block copolymer can essentially consist of a block of monomer A and a block of monomer B and a terminal group for terminating the block copolymer. The terminal group can be a hydroxy group as described above and / or a hydrogen atom as described above.

[0035] The mass ratio of monomer B to monomer A can be in the range of 20-100, in particular 30-90.

[0036] TIFF0007650799000008.tif6167 especially 80*10 3 g / mol~150*10 3 It is preferably in g / mol. TIFF0007650799000009.tif14158 where n is the number of polymer chains in the block copolymer and Mi is the molar mass of polymer chain i.

[0037] This block copolymer is commercially available from Lubrizol under the trade name Tecophilic®. An example may be Tecophilic® TG-500 and / or Tecophilic® TG-2000. The mass ratio of monomer B to monomer A is about 40 for Tecophilic® TG-500 and about 82 for Tecophilic® TG-2000. TIFF0007650799000010.tif6140Tecophilic (registered trademark) TG-500: approx. 1.4*10 5 g / mol, approximately 8*10 for Tecophilic® TG-2000 4 g / mol.

[0038] For example, the hydrogel may have a polymer used in soft contact lenses. Examples include hydroxyethyl methacrylate, methyl methacrylate, vinylpyrrolidone and / or silicone hydrogels. The hydrogel may be a thermoplastic elastomer. The hydrogel may be a smart hydrogel. In particular, the smart hydrogel may be ionic strength responsive and / or thermally responsive. An example of a smart hydrogel that is both ionic strength responsive and thermally responsive is the aforementioned Tecophilic®. Another example of a thermally responsive smart hydrogel is a polymer based on N-isopropylacrylamide copolymer.

[0039] The thickness of the diaphragm 10 may be in the range of 0.1 mm to 1.0 mm, in particular 0.35 mm to 0.7 mm.

[0040] As can be seen from FIG. 1, the composite electrode 1 includes an outer tube 4 and an outer tube 4 The composite electrode 1 has an inner tube 5 disposed within the outer tube 4. A reference space 20 in which a first conductive fluid 6 is disposed is disposed between the outer tube 4 and the inner tube 5. The composite electrode 1 also has an opening in the form of an annular gap disposed between the outer tube 4 and the inner tube 5. A diaphragm 10 is disposed in the opening and seals it.

[0041] 1 shows that the outer tube 4 has a first outer tube longitudinal end 15, and the inner tube 5 has a first inner tube longitudinal end 17, which is disposed in the region of the first outer tube longitudinal end 15. Also, a diaphragm 10 is disposed in the region of the first outer tube longitudinal end 15, and a glass membrane 9 is disposed in the region of the first inner tube longitudinal end 17.

[0042] The inner tube 5 has a second inner tube longitudinal end 16 arranged facing the opposite side to the first inner tube longitudinal end 17. Between the first inner tube longitudinal end 17 and the second inner tube longitudinal end 16, an inner tube space 19 in which the second conductive fluid 7 is arranged is arranged in the inner tube 5. Furthermore, the inner tube 5 can have a storage container 8 at its first inner tube longitudinal end 17, the inside of which forms a part of the inner tube space 19 and has a larger internal cross section than the other parts of the inner tube 5, so that a larger amount of the second conductive fluid 7 can be introduced into the inner tube 5 than in the case where the storage container 8 is not present. The thickness of the diaphragm 10 is the range of the diaphragm 10 in the direction from the first inner tube longitudinal end 17 toward the second inner tube longitudinal end 16.

[0043] If the composite electrode 1 according to FIG. 1 is a pH glass electrode, the second conductive fluid 7 can be an internal buffer solution. The internal buffer solution can have an aqueous KCl solution. As buffers, for example, acetate and / or phosphate buffers can be used. The conductive fluid 6 can have an aqueous solution, in particular an aqueous KCl solution. It is conceivable that the KCl concentration of the first electrically conductive fluid is 3 mol / l. The first conductive fluid 6 can consist of an aqueous KCl solution, or the aqueous KCl solution can be thickened with a thickener, in particular hydroxyethylcellulose, or the aqueous KCl solution can be mixed with a polymerizing monomer mixture. The polymerizing monomer mixture can be, for example, a polymer obtained by polymerization of N-acryloylaminoethoxyethanol or by copolymerization of N-acryloylaminoethoxyethanol with hydroxyalkyl methacrylate, as described in WO 2005 / 073704 A1.

[0044] The working electrode 2 and the reference electrode 3 can each be a silver-silver chloride electrode. And the pH glass electrode can have the following electrochemical series: Ag(s)|AgCl(s)|K+(aq)Cl-(aq)||glass membrane 9||measured fluid||diaphragm 10|||K+(aq)Cl-(aq)||AgCl(s)||Ag(s). Now, the electrical voltage between the two Ag(s) elements can be measured. Based on the measured voltage, a conclusion can be made about the pH value of the measured fluid.

[0045] The composite electrode 1 may comprise a plug 11 arranged in the annular gap on the side of the diaphragm 10 facing away from the reference space 20 and supporting the diaphragm 10. The plug 11 is permeable to the fluid to be measured. For this purpose, the plug 11 may have one or more plug through holes, may have a groove and / or may be porous.

[0046] As can be seen in Fig. 1, the composite electrode 1 may comprise a seal 21 which is introduced into the inner tube 5 to seal the inner tube space 19. The second conductive fluid is thus arranged between the first inner tube longitudinal end 17 and the seal 21. The seal 21 may be an adhesive, in particular a silicone adhesive.

[0047] Furthermore, the composite electrode 1 can have a sealing ring 14 arranged in the annular gap between the outer tube 4 and the inner tube 5 in the region of a second outer tube longitudinal end 18 arranged facing away from the first outer tube longitudinal end 15, and sealing the reference space 20. In this way, the first conductive fluid 6 is arranged between the diaphragm 10 and the sealing ring 14.

[0048] As can be seen from Fig. 1, the composite electrode 1 may have a head portion 12 surrounding the outer tube 4 at its second outer tube longitudinal end 18. Furthermore, the head portion 12 protrudes from the second outer tube longitudinal end 18. The head portion 12 has a hollow space therein, which is filled with a potting compound 13. In addition to the sealing ring 14 and the seal 21, the potting compound 13 serves as an additional seal. The potting compound 13 may be a silicone adhesive.

[0049] The composite electrode 1 can be manufactured as follows: providing an outer tube 4 and an inner tube 5 and placing the inner tube 5 in the outer tube 4, such that a reference space 20 is arranged between the outer tube 4 and the inner tube 5, the outer tube 4 and the inner tube 5 defining an opening having the shape of an annular gap; - placing the working electrode 2 in the inner tube 5 and the reference electrode 3 in the reference space 20; - placing a second conductive fluid 7 in the inner tube 5, the second conductive fluid 7 contacting the glass membrane 9 and the working electrode 2, so that the glass membrane 9 is electrically connected to said working electrode 2 via the second conductive fluid 7; - introducing a dry hydrogel into the opening and defining a reference volume 20 with the hydrogel; - introducing a first conductive fluid 6 into the reference space 20, thereby contacting the hydrogel with the first conductive fluid 6, so that the hydrogel swells to form a membrane 10 and seal the opening; and contacting the first conductive fluid 6 with the reference electrode 3 such that the membrane 10 is electrically connected to the reference electrode 3 via the first conductive fluid 6.

[0050] To prevent the second conductive fluid 7 from leaking out of the inner tube 5, the method comprises: - sealing the second inner tube longitudinal end 16 by means of a seal 21 and / or by means of the head 12 and potting compound 13; may have the following structure:

[0051] To introduce the first conductive fluid into the reference volume 20, a first alternative is the following approach: - introducing the first conductive fluid 6 into the reference space 20 via the second outer tube longitudinal end 18; to provide.

[0052] In order to prevent the first conductive fluid 6 from escaping from the reference space 20 through the second outer tube longitudinal end 18, the method comprises the steps of: after the introduction of the first conductive fluid into the reference space 20: sealing the second outer tube longitudinal end 18 by means of a sealing ring 14 and / or by means of the head 12 and the potting compound 13; has.

[0053] To introduce the first conductive fluid into the reference volume 20, a second alternative is the following approach: - sealing the second outer tube longitudinal end 18 before introducing the first conductive fluid 6 into the reference space 20 To provide a vacuum vessel, the first outer tube longitudinal end 15 is immersed in the first conductive fluid 6, the composite electrode 1 is introduced together with the first conductive fluid 6 into the vacuum vessel, and the vacuum vessel is evacuated and then ventilated so that the first conductive fluid 6 enters the reference space 20 through the opening. The sealing of the second outer tube longitudinal end 18 can be performed by a sealing ring 14 and / or by the head 12 and the potting compound 13. The vacuum vessel can be evacuated to a pressure of 50 mbar to 100 mbar, in particular 80 mbar.

[0054] To introduce the dry hydrogel into the opening, the following approaches can be used: in a first alternative, the inner tube 5 is first placed inside the outer tube 4, and then the hydrogel is introduced into the opening. In a second alternative, the hydrogel is first placed around the inner tube 5, and the inner tube 5 together with the hydrogel is then placed inside the outer tube 4. In a third alternative, the hydrogel is first placed inside the outer tube 4, and then the inner tube 4 is introduced into the outer tube.

[0055] When the hydrogel in a dry state is introduced into the opening, the hydrogel is smaller than the opening, and after the first conductive fluid is introduced into the reference space, a compressive stress can be generated in the formed diaphragm. In order to ensure the generation of the compressive stress, a person skilled in the art can carry out a preliminary test using hydrogels of various sizes smaller than the opening in a dry state, and then bring them into contact with the first conductive fluid to swell. After swelling, the size of the hydrogel in the swollen state is determined, and among the various sizes of hydrogels, only those that are larger than the opening in the swollen state are suitable for the diaphragm. Among the various sizes of hydrogels, it is possible to select those that are 10% to 100% larger than the opening in the swollen state, in particular those that are 30% to 50% larger. The swelling degree Q of the hydrogel can be in the range of 115% to 1000%, in particular 150% to 800%, in particular 180% to 350%. The swelling degree Q can be calculated as Q=(V Q -V T ) / V T is defined as V T is the volume of the hydrogel in the dry state, and V Q is the volume of the hydrogel swollen with the first conductive fluid.

[0056] Sixteen composite electrodes 1 were installed, and the diffusion potential, reference resistance, and outflow were examined. The results of the diffusion potential and reference resistance are summarized in Tables 1 to 3, and the results of the outflow are summarized in Table 4. Twelve of the composite electrodes (indicated as 0b, 0c, 1a, 1b, 1c, 3a, 3b, 3c, 4a, 4b, 4c, and 5a in the table) are so-called T-type composite electrodes 1, and four (indicated as 2a, 2b, 2c, and 6a in the table) are so-called P-type composite electrodes 1. In the case of the T-type composite electrode 1, the volume of the reference space 20 is about 3.5 ml, and in the case of the P-type composite electrode, the volume of the reference space 20 is about 7 ml. As can be seen from Tables 1 to 3, diaphragms with thicknesses of 0.35 mm, 2 x 0.35 mm = 0.7 mm (i.e., two layers of hydrogel were placed on top of each other), 0.50 mm, and 0.55 mm were used. For the hydrogel, Tecophilic® TG-500 and Tecophilic® TG-2000 were used. For the first conductive fluid 6, a mixture containing an aqueous KCl solution, glycerin, and hydroxyethyl cellulose was used. The composite electrode 1 according to Table 1 has a plug 11. It was easily possible to fill all 16 composite electrodes in the vacuum vessel with the first conductive fluid 6.

[0057] Diffusion potential U DIFF teeth 、 The reference resistance R was determined by measuring the composite electrode 1 against an external reference electrode. REF teeth 、 It was determined by measuring the resistance between the reference electrode 3 and the measured fluid. The measurements were performed using a 3M KCl aqueous solution, a buffer solution of pH 4, a buffer solution of pH 7, and a buffer solution of pH 10 as the measured fluid. The diffusion potential U DIFF and the reference resistor R REF was measured 1 day after washing (measurements on the left in columns 3-5 of Tables 1-3) and 30 minutes later (measurements on the right in columns 3-5 of Tables 1-3). Measurements were repeated with buffer diluted at a ratio of 1:10 (see Table 2) and 1:100 (see Table 3) compared to the buffer in Table 1. Note that "und." in Tables 2 and 3 indicates that the KCl solution was not diluted.

[0058] The fourth column of Tables 1-3 shows the maximum voltage difference ΔU of the diffusion potential measured in four different solutions. DIFF (See the corresponding third column in Tables 1 to 3). A good electrode has a maximum voltage difference ΔU of at most 3 mV. DIFF Maximum voltage difference ΔU DIFF Since the resistance of the composite electrode is 3 mV, the measurement accuracy of the composite electrode is improved. As can be seen from Tables 1 to 3, after a measurement period of 30 minutes, all 16 composite electrodes meet this criterion. Furthermore, the reference resistance U REF should not exceed 50 kOhm, but according to tables 1-3, this is also met for all electrodes. Since the reference resistance is not higher than 50 kOhm, the requirements for measuring electronic devices designed to measure the voltage between the working and measuring electrodes are not very high. In addition, the composite electrode 1 has a low diffusion potential U, the maximum amount of which is 3 mV after a measurement period of 30 minutes. DIFF Only has.

[0059] To measure the potassium flux from the reference space 20, the composite electrode 1 was stored in deionized water for 7 days, so that the diaphragm 10 was in contact with the deionized water. The amount of potassium contained in the deionized water was then measured by mass spectrometry (the third column of Table 4, in this case ICP-MS means inductively coupled plasma-mass spectrometry). Furthermore, the amount of potassium contained in the deionized water was determined by conductivity measurement (the fourth column of Table 4, in this case conv.via cond. means converted via conductivity), and the conductivity measurement was calibrated using the measurement data in the third column. The third and fourth columns of Table 4 show the amount of potassium flux per day. In FIG. 2, the amount of potassium flux (mg) per day is plotted for each composite electrode 1. T is T-type, P is P-type, TG500 is Tecophilic® TG-500, TG2000 is Tecophilic® TG-2000, and the subsequent numbers indicate the thickness of the diaphragm 10 in 10 units. -2The measurements are in mm. The following letters indicate structurally identical composite electrodes 1 and are identical to the letters in the first column of Tables 1 to 4. Table 4 and FIG. 2 show that only two of the composite electrodes 1 (T-TG500-35-B and P-TG500-35-C) have a potassium efflux of more than 0.5 mg per day. This can be explained by the fact that the diaphragm 10 was accidentally slightly damaged when introducing it into the opening. It can also be seen that the amount of potassium efflux decreases as the thickness of the diaphragm 10 increases.

[0060] FIG. 3 shows the potassium flux of a further composite electrode 1, which is a composite electrode 1 of type M. One of the composite electrodes 1 of type M is a conventional composite electrode with a porous ceramic diaphragm (labeled "ceramic" in FIG. 3). In FIG. 3, the potassium flux (mg / day) is plotted for each composite electrode 1. M stands for type M, TG500 stands for Tecophilic® TG-500, TG2000 stands for Tecophilic® TG-2000, and the subsequent numbers represent the thickness of the diaphragm in 10 units. -2 The dimensions are expressed in mm. The subsequent letters indicate structurally identical composite electrodes 1. The M-type composite electrode 1 is different from the T-type composite electrode 1 and the P-type composite electrode 1 in that the outer diameter of the inner tube 5 and the inner diameter of the outer tube 4 are shorter than those of the T-type composite electrode 1 and the P-type composite electrode 1. For each of the M-type composite electrodes 1, the potassium flux was measured when the temperature of deionized water was 21°C (left bar) and 37°C (right bar). The respective potassium fluxes are shown under the bars, and the larger numbers are the potassium fluxes at 37°C. From FIG. 3, it can be seen that the potassium flux when the Tecophilic® diaphragm was used is smaller than that when the porous ceramic diaphragm was used.

[0061] It has also been shown that it is possible to fill the reference space 20 in the vacuum vessel with a 3M aqueous solution of KCl. It has also been shown that it is possible to introduce a solid electrolyte into the reference space 20 in the vacuum vessel. For this purpose, the reference space 20 is filled with a monomer mixture which is subsequently polymerized to form the solid electrolyte. The solid electrolyte can be, for example, a polymer obtained by polymerizing N-acryloylaminoethoxyethanol or by copolymerizing N-acryloylaminoethoxyethanol with a hydroxyalkyl methacrylate, as described in WO 2005 / 073704 A1.

[0062] [Table 1] TIFF0007650799000012.tif196161

[0063] [Table 2] TIFF0007650799000014.tif203160

[0064] [Table 3] TIFF0007650799000016.tif204162

[0065] [Table 4] TIFF0007650799000018.tif70161

[0066] List of reference symbols 1 Composite electrode 2 working electrode 3 Reference electrode 4 Outer tube 5 Inner tube 6 First conductive fluid 7 Second Conductive Fluid 8. Storage Containers 9 Glass membrane 10 Diaphragm 11 Plug 12 Head section 13 Potting compound 14 Sealing ring 15 First outer tube longitudinal end 16 Second inner pipe longitudinal end 17 First inner pipe longitudinal end 18 Second outer tube longitudinal end 19 Inner tube space 20 Reference space 21 Seal

Claims

1. A composite electrode (1) for measuring a fluid to be measured, the composite electrode (1) having a working electrode (2), a reference electrode (3), a diaphragm (10), and a first conductive fluid (6) in contact with the reference electrode (3) and the diaphragm (10), the diaphragm (10) being electrically connected to the reference electrode (3) via the first conductive fluid (6), the diaphragm (10) having a hydrogel, the composite electrode (1) having a reference space (20) in which the first conductive fluid (6) is disposed, and an opening in which the diaphragm (10) is disposed and sealed by the diaphragm (10), the hydrogel introduced into the opening in a dry state swells after contact with the first conductive fluid (6) to seal the opening.

2. The composite electrode (1) according to claim 1, wherein the hydrogel comprises a thermoplastic polyurethane.

3. 3. The composite electrode (1) according to claim 2, wherein the thermoplastic polyurethane is made of monomer A. and Monomer B A composite electrode (1) which is a block copolymer having the following structure:

4. The composite electrode (1) according to claim 3, wherein the mass ratio of said monomer B to said monomer A is in the range of 20-100.

5. The composite electrode (1) according to claim 3, wherein the mass ratio of said monomer B to said monomer A is in the range of 30-90.

6. A composite electrode (1) according to any one of claims 3 to 5, A composite electrode (1) having a range of

7. A composite electrode (1) according to any one of claims 3 to 5, 80*10 3 g / mol~150*10 3 g / mol range, composite electrode (1).

8. 2. The composite electrode (1) according to claim 1, wherein the hydrogel comprises a polymer based on hydroxyethyl methacrylate, vinylpyrrolidone and / or silicone.

9. The composite electrode (1) according to any one of the preceding claims, wherein the hydrogel is a thermoplastic elastomer.

10. The composite electrode (1) according to any one of the preceding claims, wherein the hydrogel is a smart hydrogel.

11. The composite electrode (1) according to claim 10, wherein the smart hydrogel is ionic strength responsive and / or thermoresponsive.

12. 11. A composite electrode (1) according to claim 10, comprising an outer tube (4) and an inner tube (5) arranged within the outer tube (4), the reference space (20) being arranged between the outer tube (4) and the inner tube (5), and the opening being an annular gap between the outer tube (4) and the inner tube (5).

13. 13. A composite electrode (1) according to claim 10 or 12, comprising a plug (11) that is permeable to the fluid to be measured and that is disposed in the opening and supports the diaphragm (10).

14. 13. The composite electrode (1) according to claim 12, wherein the inner tube (5) has a first inner tube longitudinal end (17) designed to be closed and a glass membrane (9), and a second conductive fluid (7) that brings the glass membrane (9) into contact with the working electrode (2) is arranged in the inner tube (5) such that the glass membrane (9) is electrically connected to the working electrode (2) via the second conductive fluid (7).

15. The composite electrode (1) according to any one of the preceding claims, wherein the composite electrode (1) is a pH composite electrode and / or a redox sensor.

16. 16. The composite electrode (1) according to claim 15, wherein the composite electrode (1) is a pH composite electrode, and the pH composite electrode is a pH glass electrode.

17. A method for manufacturing a composite electrode (1), said method comprising the steps of: providing an outer tube (4) and an inner tube (5) arranged within said outer tube (4), a reference space (20) being arranged between said outer tube (4) and said inner tube (5), said outer tube (4) and / or said inner tube (5) defining an opening; placing a working electrode (2) in the inner tube (5) and a reference electrode (3) in the outer tube (4); introducing a dry hydrogel into said opening so as to define said reference volume (20) with said hydrogel; a step of introducing a first conductive fluid (6) into the reference space (20) and contacting the hydrogel with the first conductive fluid (6), whereby the hydrogel swells to form a membrane (10) and seals the opening; and a step of contacting the reference electrode (3) with the first conductive fluid (6), whereby the membrane (10) is electrically connected to the reference electrode (3) via the first conductive fluid (6). The method comprising:

18. 18. The method according to claim 17, wherein the outer tube (4) has a first outer tube longitudinal end (15) in the area where the diaphragm (10) is located and a second outer tube longitudinal end (18), and the first conductive fluid (6) is introduced into the reference space (20) via the second outer tube longitudinal end (18).

19. 18. The method according to claim 17, wherein the outer tube (4) has a first outer tube longitudinal end (15) in the region where the membrane (10) is arranged and a second outer tube longitudinal end (18), the method comprising the steps of: sealing the second outer tube longitudinal end (18) before introducing the first conductive fluid (6) into the reference space (20). having In order to introduce the first conductive fluid (6) into the reference space (20), the longitudinal end (15) of the first outer tube is immersed in the first conductive fluid (6), the composite electrode (1) is introduced into a vacuum vessel together with the first conductive fluid (6), and the vacuum vessel is evacuated and then ventilated so that the first conductive fluid (6) enters the reference space (20) through the opening. method.

20. The method according to any one of claims 17 to 19, wherein the inner tube (5) has a first inner tube longitudinal end (17) designed to be closed and a glass membrane (9) arranged in the area of ​​the first inner tube longitudinal end (17), and a second conductive fluid (7) that brings the glass membrane (9) into contact with the working electrode (2) is arranged in the inner tube (5) in such a way that the glass membrane (9) is electrically connected to the working electrode (2) via the second conductive fluid (7).

21. The method according to any one of claims 17 to 20, wherein when the hydrogel in a dry state is introduced into the opening, the hydrogel is smaller than the opening and the formed membrane (10) is under compressive stress after the first conductive fluid (6) is introduced into the reference space (20).

Citation Information

Patent Citations

  • Compact solid-state reference electrode with self-diagnostic function

    JP2002540424A

  • Ion-selective electrode and reference electrode

    JP2005274182A

  • Reference electrode, salt bridge, and ion concentration measuring device using them

    JP2007064971A

  • Polymer reference electrode

    JP2008514903A

  • In vivo specific ion sensor

    US3957612A